2016
DOI: 10.15171/jrip.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Renal biochemical and histopathological alterations of diabetic rats under treatment with hydro alcoholic Morus nigra extrac

Abstract: Introduction: Morus nigra fruit is known to have antioxidant effects and used to control the blood sugar level in traditional medicine. Objectives: This study was conducted to investigate the biochemical and histopathological changes in the serum and kidneys of diabetic rats treated with hydroalcoholic M. nigra extract. Materials and Methods: In this study, 60 male Wistar rats were divided into five groups of 12 each. After induction of diabetes with alloxan, the diabetic rats were treated with hydroalcoholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Long‐term hyperglycaemia is known as the driving force for glycogen accumulations in the renal tubules of diabetic rats. [ 62 ] According to the present histopathological examination, there is amelioration of glycogen accumulation and fatty degeneration of renal tubules in diabetic rats treated with BMFE, which comes in agreement with the results reported by Rahimi‐Madiseh [ 24 ] who documented that hydroalcoholic extract of M. nigra fruit may prevent damage to the kidney tissue but at higher dose (800 mg/Kg), far from the doses used in the current study. In a similar study using water extract of green tea as an antioxidant, the diabetic‐treated rats showed amelioration of the histopathological changes like fatty degeneration of renal tubule relative to diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Long‐term hyperglycaemia is known as the driving force for glycogen accumulations in the renal tubules of diabetic rats. [ 62 ] According to the present histopathological examination, there is amelioration of glycogen accumulation and fatty degeneration of renal tubules in diabetic rats treated with BMFE, which comes in agreement with the results reported by Rahimi‐Madiseh [ 24 ] who documented that hydroalcoholic extract of M. nigra fruit may prevent damage to the kidney tissue but at higher dose (800 mg/Kg), far from the doses used in the current study. In a similar study using water extract of green tea as an antioxidant, the diabetic‐treated rats showed amelioration of the histopathological changes like fatty degeneration of renal tubule relative to diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
“…Black mulberry leaves, fruits and barks are used in certain areas of the world as antidiabetic remedies, and recent investigations have proved their efficacy in lowering blood glucose levels in diabetic animals and to less extent in human subjects. [ 23–25 ] Phytochemical investigations of BMFE identified two anthocyanins: cyanidin 3‐ O‐β‐ glucoside and cyanidin 3‐ O‐β‐ rutinoside as the two major constituents of BMFE and juice [ 33,38,39 ] albeit with variable concentrations based on the geographical origin and the variety used. BMFE used in this study showed the same chemical profile of anthocyanins as outlined in Figure 1 and Table .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of hydroalcoholic extract of M. nigra fruits on biochemical and histopathological changes in serum and kidney tissues have been evaluated in alloxan-induced diabetic rats [ 69 ]. Milder glomerular damage and no mesenchymal tissue expansion into renal glomerular vessels were observed in the group after 8 weeks of treatment with 800 mg/kg M. nigra fruit extract compared to those in diabetic and positive control (150 mg/kg metformin) groups.…”
Section: Organ-protective Activitymentioning
confidence: 99%
“…On the other side, histopathology study of kidney tissues were revealed degeneration in alloxan induced tissues after treatment of extract on these group, degeneration had become normal. 49,50 …”
Section: Discussionmentioning
confidence: 99%